A robust design of a numerically demanding compact rat‐race coupler. Issue 5 (May 2014) - Kurgan, Piotr; Bekasiewicz, Adrian
ABSTRACT A fast and accurate design procedure of a computationally expensive microwave circuit has been presented step‐by‐step and experimentally validated on the basis of a compact rat‐race coupler (RRC) comprising slow‐wave resonant structures. The final compact RRC solution has been obtained by means of a sequential optimization scheme exploiting the implicit space mapping algorithm. A well‐suited surrogate optimization starting point as well as a considerable limitation of the surrogate optimization variables contribute significantly to the numerical efficiency of the method proposed. The final design, offering 85% size reduction together with a satisfactory performance, has been obtained with only a handful of EM simulations. The experimental validation of the method has been successfully conducted. © 2014 Wiley Periodicals, Inc. Microwave Opt Technol Lett 56:1259–1263, 2014